The center of olfactory bulb‐seeded α‐synucleinopathy is the limbic system and the ensuing pathology is higher in male than in female mice - Mason, Daniel M. (Brain Pathol, 2019)
At early disease stages, Lewy body disorders are characterized by limbic vs. brainstem α‐synucleinopathy, but most preclinical studies have focused solely on the nigrostriatal pathway. Furthermore, male gender and advanced age are two major risk factors for this family of conditions, but their influence on the topographical extents of α‐synucleinopathy and the degree of cell loss are uncertain. To fill these gaps, we infused α‐synuclein fibrils in the olfactory bulb/anterior olfactory nucleus complex—one of the earliest and most frequently affected brain regions in Lewy body disorders—in 3‐month‐old female and male mice and in 11‐month‐old male mice. After 6 months, we observed that α‐synucleinopathy did not expand significantly beyond the limbic connectome in the 9‐month‐old male and female mice or in the 17‐month‐old male mice. However, the 9‐month‐old male mice had developed greater α‐synucleinopathy, smell impairment and cell loss than age‐matched females. By 10.5 months post‐infusion, fibril treatment hastened mortality in the 21.5‐month‐old males, but the inclusions remained centered in the limbic system in the survivors. Although fibril infusions reduced the number of cells expressing tyrosine hydroxylase in the substantia nigra of young males at 6 months post‐infusion, this was not attributable to true cell death. Furthermore, mesencephalic α‐synucleinopathy, if present, was centered in mesolimbic circuits (ventral tegmental area/accumbens) rather than within strict boundaries of the nigral pars compacta, which were defined here by tyrosine hydroxylase immunolabel. Nonprimate models cannot be expected to faithfully recapitulate human Lewy body disorders, but our murine model seems reasonably suited to (i) capture some aspects of Stage IIb of Lewy body disorders, which displays a heavier limbic than brainstem component compared to incipient Parkinson’s disease; and (ii) leverage sex differences and the acceleration of mortality following induction of olfactory α‐synucleinopathy.